Efficacy of Hormonal and Nonhormonal Approaches to Vaginal Atrophy and Sexual Dysfunctions in Postmenopausal Women: A Systematic Review - Sarmento, Ayane Cristine Alves; Costa, Ana Paula Ferreira; Lírio, Juliana; Eleutério Jr, José; Baptista, Pedro Vieira; Gonçalves, Ana Katherine (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To evaluate the efficacy of the hormonal and nonhormonal approaches to symptoms of sexual dysfunction and vaginal atrophy in postmenopausal women.Data Sources We conducted a search on the PubMed, Embase, Scopus, Web of Science, SciELO, the Cochrane Central Register of Controlled Trials (CENTRAL), and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases, as well as on clinical trial databases. We analyzed studies published between 1996 and May 30, 2020. No language restrictions were applied.Selection of Studies We selected randomized clinical trials that evaluated the treatment of sexual dysfunction in postmenopausal women.Data Collection Three authors (ACAS, APFC, and JL) reviewed each article based on its title and abstract. Relevant data were subsequently taken from the full-text article. Any discrepancies during the review were resolved by consensus between all the listed authors.Data Synthesis A total of 55 studies were included in the systematic review. The approaches tested to treat sexual dysfunction were as follows: lubricants and moisturizers (18 studies); phytoestrogens (14 studies); dehydroepiandrosterone (DHEA; 8 studies); ospemifene (5 studies); vaginal testosterone (4 studies); pelvic ﬂoor muscle exercises (2 studies); oxytocin (2 studies); vaginal CO2 laser (2 studies); lidocaine (1 study); and vitamin E vaginal suppository (1 study).Conclusion We identified literature that lacks coherence in terms of the proposed treatments and selected outcome measures. Despite the great diversity in treatment modalities and outcome measures, the present systematic review can shed light on potential targets for the treatment, which is deemed necessary for sexual dysfunction, assuming that most randomized trials were evaluated with a low risk of bias according to the Cochrane Collaboration risk of bias tool. The present review is registered with the International Prospective Register of Systematic Reviews (PROSPERO; CRD42018100488).
Keywords: menopause; dyspareunia; orgasm; therapeutics; estrogens